Venus On Venus: CKUT’s Women’s Collective Music Show Dishes on Feminist Radio - Leventhal, Anna; McInnis, Catherine; Wilson, Angela (Women in Radio: Unfiltered Voices from Canada, 2020)
Three volunteer hosts and programmers of a feminist music show at a campus-community radio station, Anna Leventhal, Catherine McInnis, and Angela Wilson, sat down in 2008 to chat about feminist radio. They discussed the concept of a feminist music show and the possibilities and limitations of female-only spaces; the “fem-con” concept that campus-community radio stations be mandated to play a certain amount of music by women, in the same way they are mandated by the CRTC to play Canadian content; the transformative social and political potential of community radio; and the inclusion of trans and gender-nonconforming voices on the show.